2019
DOI: 10.1101/845701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological responses to light explain competition and facilitation in a tree diversity experiment

Abstract: 14Author contributions: SK conceived the project with JCB, conducted physiological measurements, 15analyzed and interpreted the data with JCB and RM, and wrote the first draft of the paper. JCB and RM 16designed the FAB experiment, coordinated annual biomass surveys, and contributed to subsequent 17 revisions of the paper. 19Summary 20  Interspecific facilitation is often invoked in explanations of biodiversity-ecosystem function 21 relationships in plant communities, but it is seldom clear how it occurs. Phy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 111 publications
0
15
0
1
Order By: Relevance
“…In the first, the papers explore the facilitative mechanisms that underlie the effect that biodiversity has on productivity. For example, Kothari et al (2021) isolate the suppressive effects of photoinhibition in monoculture to help explain biodiversity – productivity relationships in forested ecosystems. Guimarães‐Steinicke et al (2021) use hyperspectral data to examine how diversity and functional identity affect leaf surface temperatures in grasslands.…”
Section: Papers In This Special Featurementioning
confidence: 99%
“…In the first, the papers explore the facilitative mechanisms that underlie the effect that biodiversity has on productivity. For example, Kothari et al (2021) isolate the suppressive effects of photoinhibition in monoculture to help explain biodiversity – productivity relationships in forested ecosystems. Guimarães‐Steinicke et al (2021) use hyperspectral data to examine how diversity and functional identity affect leaf surface temperatures in grasslands.…”
Section: Papers In This Special Featurementioning
confidence: 99%
“…Subordinate species' LUE may increase in mixture if they intercept less light without a proportional decrease in growth; a phenomenon anticipated by the photosynthetic light-response curve if the species shifts (to lower irradiance) along a flat part of their curve or if shading reduces photoinhibition (Kothari et al 2020) (Fig. S8).…”
Section: Falsementioning
confidence: 99%
“…Enhanced productivity in species mixtures relative to monocultures (i.e. overyielding) may arise in many ways, including competitive relaxation via resource partitioning (Richards & Schmidt 2010;Sapijanskas et al 2014; Barry et al 2019), competitive imbalance leading to the dominance of a highly productive species (Yachi & Loreau 2007), facilitation that ameliorates nutrient, microclimatic or light stress (Tilman et al 1997;Cowles et al 2016;Wright et al 2017;Kothari et al 2020), plant-soil interactions that enhance soil resource availability (Reich et al 2012;Cowles et al 2016), and trophic interactions that increase plant fitness (Laforest-Lapointe et al 2017) or reduce herbivory or disease (Jactel & Brockerhoff 2007;Jactel et al 2017). Here we focus on how interactions among trees for a single resourcelightcan lead to overyielding in mixed-species forests.…”
Section: Introductionmentioning
confidence: 99%
“…After this, competitive interactions should prevail even in the originally resource-poor sites (Olsen et al 2016). Alternatively, previous studies also indicated that light disturbance may lead to higher stress for understory shade-tolerant plant species due to extreme temperatures, higher air vapour pressure deficits and light excesses, that might support facilitation after canopy opening (Wright et al 2015, Kothari et al 2021). However, we did not observe any changes in the competition-facilitation balance either towards competition or towards facilitation over time.…”
Section: Linking Competition-faciliation Gradient To Microtopographymentioning
confidence: 99%